1998
DOI: 10.1073/pnas.95.5.2568
|View full text |Cite
|
Sign up to set email alerts
|

The chemotaxis system, but not chemotaxis, is essential for swarming motility in Escherichia coli

Abstract: The chemotaxis system plays an essential role in swarm cell differentiation and motility. We show in this study that two (Tsr and Tar) of the four chemoreceptors in Escherichia coli can support swarming individually, but sensing their most powerful chemoattractants is not necessary. Conditions that abolish chemotaxis toward serine (presence of serine concentrations that saturate Tsr, or mutations in Tsr that destroy serine binding) have no effect on swarming. Similar results were obtained for the aspartate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
129
2
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(142 citation statements)
references
References 42 publications
8
129
2
3
Order By: Relevance
“…In E. coli, the signal transduction system is essential for swarming motility but traditional chemotaxis is not (44). Recently, it has been proposed that the twitching motility of P. aeruginosa and the social gliding motility of Myxococcus xanthus are essentially the same type IV pili-based process (45).…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli, the signal transduction system is essential for swarming motility but traditional chemotaxis is not (44). Recently, it has been proposed that the twitching motility of P. aeruginosa and the social gliding motility of Myxococcus xanthus are essentially the same type IV pili-based process (45).…”
Section: Discussionmentioning
confidence: 99%
“…As described in the introduction to this report, M. xanthus is one of the best-studied gliding bacteria. Swarming motility is widespread among eubacteria (16,17) and has been extensively studied in Vibrio parahaemolyticus, Proteus mirabilis (1,7,24), and recently in Serratia liquefaciens, Escherichia coli, and Salmonella typhimurium (8,15,16). On appropriate surfaces, these bacteria undergo a series of changes and transform from "swimmer" cells to differentiated "swarmer" cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial cell elongation occurs after treatment with ␤-lactam antibiotics, such as cephalexin (13,24,28,30), from mutations in the cell division gene lonS (32), or upon differentiation to swarmer cells (3,6,9,15,25). We have previously reported that the MCPs of cephalexin-treated E. coli cells are localized not only to the cell poles but also at intervals along the length of the elongated cell (24).…”
mentioning
confidence: 99%